Relaxin Activates Peroxisome Proliferator-activated Receptor γ (PPARγ) through a Pathway Involving PPARγ Coactivator 1α (PGC1α) - Singh, Sudhir (J Biol Chem, 2015)
Relaxin activation of its receptor RXFP1 triggers multiple signaling pathways. Previously, we have shown that relaxin activates PPARγ transcriptional activity in a ligand-independent manner, but the mechanism for this effect was unknown. In this study, we examined the signaling pathways of downstream of RXFP1 leading to PPARγ activation. Using cells stably expressing RXFP1, we found that relaxin regulation of PPARγ activity requires accumulation of cAMP and subsequent activation of cAMP-dependent protein kinase (PKA). The activated PKA subsequently phosphorylated cAMP response element-binding protein (CREB) at Ser-133 to activate it directly, as well as indirectly through mitogen activated protein kinase p38 MAPK. Activated CREB was required for relaxin stimulation of PPARγ activity, while there was no evidence for a role of the nitric oxide or ERK MAPK pathways. Relaxin increased the mRNA and protein levels of the coactivator protein PGC1α, and this effect was dependent on PKA, and was completely abrogated by a dominant-negative form of CREB. This mechanism was confirmed in a hepatic stellate cell line stably that endogenously expresses RXFP1. Reduction of PGC1α levels using siRNA diminished the regulation of PPARγ by relaxin. These results suggest that relaxin activates the cAMP/PKA and p38 MAPK pathways to phosphorylate CREB, resulting in increased PGC1α levels. This provides a mechanism for the ligand-independent activation of PPARγ in response to relaxin.